1997
DOI: 10.1038/sj.bjp.0701472
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of tolerance to the antitransit effects of morphine during acute intestinal inflammation in mice

Abstract: 1 The aim of investigation was to establish and compare the reversibility of tolerance to the antitransit e ects of morphine by three di erent procedures: (a) acute in¯ammation of the gut, (b) lorglumide a cholecystokinin A (CCK A ) receptor antagonist, or (c) MK-801, an N-methyl-D-aspartate (NMDA) receptor ion channel blocker. The type of interaction between morphine and lorglumide or MK-801 on the inhibition of gastrointestinal transit (GIT) in naive animals was also evaluated. 2 Male Swiss CD-1 mice were im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…However, the apparent reversal of tolerance may be related to the observations that conditions of inflammation are associated with reduced availability of CCK and enhanced activity of morphine (Stanfa et al, 1994;Ossipov et al, 1995a;Vanderah et al, 1996a). This interpretation is consistent with the fact that CCK antagonists reversed tolerance to morphine-induced inhibition of GI motility (Pol and Puig, 1997).…”
Section: Nociceptive Actions Of Opioidssupporting
confidence: 80%
See 1 more Smart Citation
“…However, the apparent reversal of tolerance may be related to the observations that conditions of inflammation are associated with reduced availability of CCK and enhanced activity of morphine (Stanfa et al, 1994;Ossipov et al, 1995a;Vanderah et al, 1996a). This interpretation is consistent with the fact that CCK antagonists reversed tolerance to morphine-induced inhibition of GI motility (Pol and Puig, 1997).…”
Section: Nociceptive Actions Of Opioidssupporting
confidence: 80%
“…Nevertheless, the analgesic effect of intraarticular morphine in this population, leading to the assertion that opioid peptides expressed in inflamed tissue do not produce tolerance to peripheral morphine (Stein et al, 1996). In a study of gastrointestinal (GI) transit in mice, it was found that intestinal inflammation reversed tolerance to morphine-induced inhibition of GI motility (Pol and Puig, 1997). However, the apparent reversal of tolerance may be related to the observations that conditions of inflammation are associated with reduced availability of CCK and enhanced activity of morphine (Stanfa et al, 1994;Ossipov et al, 1995a;Vanderah et al, 1996a).…”
Section: Nociceptive Actions Of Opioidsmentioning
confidence: 97%
“…For the induction of tolerance, a 75-mg morphine pellet was implanted subcutaneously (Pol and Puig, 1997) that induced steady morphine plasma levels without the intermittent periods of abstinence or changes in nociceptive behavior observed when a daily injection protocol is used (Li and Clark, 2002). This method of morphine administration closely reproduces the clinical situation where patients are exposed to therapeutic plasma levels of opioids (e.g., slowrelease formulations and transdermal patches) capable of controlling pain in a continuous manner.…”
Section: Morphine Tolerance In a Model Of Peripheral Inflammation 365mentioning
confidence: 99%
“…Morphine tolerance was induced by the s.c. implantation of a 75-mg morphine pellet (Pol and Puig, 1997;Bohn et al, 2002), whereas control animals received a placebo pellet. Under halothane anesthesia, a small skin pocket was dissected in the back of the animal, where a single pellet was inserted, and the skin was closed with surgical sutures.…”
Section: Behavioral Testingmentioning
confidence: 99%
See 1 more Smart Citation